Post mortem histological artifacts created by poor tissue handling during necropsy. (June 2014) - Venne, Penny; John-Baptiste, Annette; Vitsky, Allison
<x content-type="archive" xml:space="preserve">Abstract</x> Histological artifacts may be introduced into the tissue of laboratory animals during sample collection at the time of necropsy or during tissue processing. To identify and characterize tissue artifacts, modifications in necropsy/tissue processing standard operating procedures were made in order to reproduce some of these effects in the lungs, thyroid glands, and stomach of rats; the liver, spleen, and kidney of dogs; and the liver and spleen of non-human primates. Induced artifacts included lungs over-infused with formalin, stomachs subjected to mechanical damage, and thyroid glands roughly handled with forceps. Oversized sections of liver, spleen, and kidney tissues were forced into cassettes. All tissues were preserved for 24 hours in formalin before trimming. These tissues were processed, embedded in paraffin wax, sectioned, and stained with hematoxylin and eosin (H&E). Tissues were then examined microscopically by a pathologist and compared with control tissues collected at necropsy under standard conditions. The evaluation confirmed that artifacts such as those induced in this study can interfere with accurate histologic examination, ultimately confounding pathology interpretation. These results emphasize the importance of rigorous necropsy and tissue collection practices to ensure a consistently high quality of tissue specimens.